Adsorption of mercury (II) from aqueous solutions using FeS and pyrite: A comparative study. (October 2017) - Sun, Yue; Lv, Dan; Zhou, Jiasheng; Zhou, Xiaoxin; Lou, Zimo; Baig, Shams Ali; Xu, Xinhua
Abstract: In this study, a comparative evaluation of synthetic FeS and natural pyrite was performed to investigate their adsorptive potentials toward Hg(II) in aqueous system. Characterization analyses such as BET, SEM and TEM suggested that FeS had porous structures with abundant active sites, while pyrite with a hard and smooth surface relied mainly on surface adsorption to immobilize Hg(II). Results of batch tests revealed that FeS offered much greater Hg(II) maximum adsorption capacity (769.2 mg/g) as compared to pyrite (9.9 mg/g). Both iron sulfides showed high removal efficiency (>96%) with the initial Hg(II) concentration (1 mg/L) at pH = 7.0 ± 0.1, and the effluent could meet the permissible effluent concentration (<50 μg/L). Condition experiments (such as pH, co-ions) proved that the adaptive capacity of FeS was significantly higher than that of pyrite. A pseudo-second-order kinetic model was better able to illustrate the sorption kinetics on both FeS and pyrite (R 2  ≥ 0.9992). XRD and XPS analyses supported that precipitation, ion exchange and surface complexation were main reaction mechanisms involved in the adsorption process. In addition, it was also revealed that the structural changes of FeS before and after adsorption was much larger than pyrite. Findings from this study suggest FeS is a promising candidate for treatment of high-concentration Hg(II)-containing wastewater (<20 mg/L), while pyrite can be applied as a long-term adsorbing material in the immobilization of wastewater containing low Hg(II) concentration (<1 mg/L) due to its cost-effective property and local availability. Graphical abstract: Highlights: Both FeS and pyrite had high removal efficiency to adsorb Hg(II) from aqueous solution. FeS was more effective to treat high-concentration Hg(II) wastewater. Pyrite could apply a long-term adsorption due to its stable structure. The adaptive capacity to environment on FeS was much more outstanding. Surface adsorption controlled the mercury adsorption rate.